Development of molecular tools based on the dopamine D3 receptor ligand FAUC 329 showing inhibiting effects on drug and food maintained behavior. Issue 13 (1st July 2017) - Stößel, Anne; Brox, Regine; Purkayastha, Nirupam; Hübner, Harald; Hocke, Carsten; Prante, Olaf; Gmeiner, Peter
Graphical abstract: Abstract: Dopamine D3 receptor-mediated networks have been associated with a wide range of neuropsychiatric diseases, drug addiction and food maintained behavior, which makes D3 a highly promising biological target. The previously described dopamine D3 receptor ligand FAUC 329 (1 ) showed protective effects against dopamine depletion in a MPTP mouse model of Parkinson's disease. We used the radioligand[ 18 F]2, a [ 18 F]fluoroethoxy substituted analog of the lead compound1 as a molecular tool for visualization of D3 -rich brain regions including the islands of Calleja. Furthermore, structural modifications are reported leading to the pyrimidylpiperazine derivatives3 and9 displaying superior subtype selectivity and preference over serotonergic receptors. Evaluation of the lead compound1 on cocaine-seeking behavior in non-human primates showed a substantial reduction in cocaine self-administration behavior and food intake.